STEM-09. CANCER STEM CELL IMMUNOEDITING. (5th November 2018) - Sayour, Elias; Yang, Changlin; Grippin, Adam; Mendez-Gomez, Hector; Dajac, Mariana; Nazareth, Brian; Andrews, Michael; Loche, Tyler; Karachi, Aida; Stover, Brian; Moore, Ginger; Kresak, Jesse; et al.
Abstract: INTRODUCTION: Conventional therapies most effectively eliminate highly proliferative tumor cells but leave behind residual slow-cycling cancer stem cells (SCCs) that evade treatment and ultimately seed disease recurrence. We reported the existence of SCCs that exhibit enhanced invasiveness, tumorigenicity and resistance to therapy in glioblastoma (GBM). The increased tumorigenicity of these GBM SCC suggests they may have enhanced immunoediting capacity. OBJECTIVES: We speculate that GBM SCCs drive disease progression and recurrence through immune escape. The objective of this study is to characterize the GBM SCC interface with the immune system and identify immunosuppressive mechanisms employed by these cells. METHODS: SCCs were isolated from mouse and human models of malignant glioma and separated by flow cytometry based on their ability to retain CellTrace labeling. RESULTS: Draining lymph nodes from animals bearing SCC-derived malignant gliomas showed decreased CD8 + and increased CD4 + /Foxp3 + cells. Immune gene signature analysis of tumor infiltrates uncovered enhanced recruitment of macrophages to SCC-derived tumors, with ApoE being the most over-expressed. ApoE promotes macrophage polarization toward the immunosuppressive M2 phenotype and inhibits T cell interferon-(IFN)-γ secretion. Using the IFN-γ reporter (GREAT) mice, we found that tumors derived from SCCs repressed IFN-γ secretion/expression by in vivo imaging, ELISA and RNA sequencing. This correlated with the up-regulation of gene networks in SCCs involved in immunosuppression, specifically CSF1 a prominent survival factor for macrophages. CONCLUSION: The immune surveillance hypothesis suggests that oncogenesis, driven by cancer cell immunoediting, shapes the immune system toward a pro-tumorigenic phenotype. Our study indicates that SCCs play a pivotal role in shifting the GBM immune milieu toward a regulatory phenotype characterized by M2 macrophages polarized by ApoE signaling.